(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2020)
Background of the Study: The current focus of research is on corticosteroids thatcan improve skin conditions with its anti-inflammatory and immunosuppressive action. Objectives: To obtain information on number of drugs prescribed, their prescribing patterns, duration of treatment and rationality of drug use and side effects of corticosteroids. Study Design, Study Period & Study Site: A prospective observational case series study was conducted from july- 2019- february -2020 at MIMS (Maharaja Institute of Medical Sciences) Nellimarla , Vizianagaram. Methodology: A total of 280 patients the study is being conducted in the department of dermatology. The participants enrolled in the study involve inpatients and outpatients only after filling a properly written informed consent. The data is collected in a pre-designed data collection form. Results: A total 280 prescriptions were analyzed having 275 corticosteroids and among them 32.1% were male and 67.9% were females. Majority of patients were between the range of 21-30 years (25.71%) and 31-40 years (14.2%) and 41-50 years (11.7%). Clobetasol was found to be the most prescribed drug (86%) followed by betamethasone (68%). Most drugs were prescribed rationally some factors like drug administration time were deviating from rationality. Conclusion: Although most of the drugs were prescribed rationally, involvement of clinical pharmacists in patient care can help in more rational prescribing along with prevention and early detection of side effects which can directly promote drug safety and better patient outcomes.